A Cross-Section of the Work of Jeffrey C. Alexander - Balon, Jan (Teorie vědy / Theory of Science, 2013)
conference reportPrůřez tvorbou Jeffreyho C. Alexandera. Slovenská sociologická společnost. Bratislava, 7. prosince 2012.